MBRS-01. DISSECTING REGULATORS OF THE ABERRANT POST-TRANSCRIPTIONAL LANDSCAPE IN MYC-AMPLIFIED GROUP 3 MEDULLOBLASTOMA. (4th December 2020) - Kameda-Smith, Michelle; Zhu, Helen; Luo, EnChing; Venugopal, Chitra; Xella, Agata; Brown, Kevin; Fox, Raymond; Yee, Brian; Xing, Sansi; Tan, Frederick; Bakhshinyan, David; Adile, Ashley; et al.
Abstract: Medulloblastoma (MB) is the most common solid malignant pediatric brain neoplasm, with Group 3 (G3) MB representing the most aggressive subgroup. MYC amplification is an independent poor prognostic factor in G3 MB, however, therapeutic targeting of the MYC pathway remains limited and alternative therapies for G3 MB are urgently needed. Here we show that an RNA-binding protein, Musashi-1 (MSI1) is an essential mediator of G3 MB in both MYC -overexpressing mouse models and patient-derived xenografts. Unbiased integrative multi-omics analysis of MSI1 function in human G3 MB suggests a paradigm shift beyond traditional gene-based profiling of oncogenes. Here we identify MSI1 as an oncogene in G3 MB driving stem cell self-renewal through stabilization of HIPK1 mRNA, a downstream context-specific therapeutic target for drug discovery.